PENGARUH KESELAMATAN DAN KESEHATAN KERJA, LINGKUNGAN KERJA, DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA PT. MITRA BETON MANDIRI PEKANBARU) - Aqil Farid J.J; Restu Restu; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine The Effect of Occupational Safety and Health, WorkEnvironment, and Workload on Employees Performance at PT. Mitra BetonMandiri Pekanbaru. This study uses a census sampling technique in which thesampling technique uses the entire population as the research sample. Thesamples in this study were all factory employees at BP I PT. Mitra Beton MandiriPekanbaru, totaling 60 people. The data obtained were collected using aquestionnaire which was then analyzed using a multiple linear regression analysisapproach with the help of the SPSS program. The results showed that: 1) there isa positive and significant effect between the independent variables (OccupationalSafety and Health, Work Environment, and Workload) simultaneously or togetheron the dependent variable (Employees Performance) at PT. Mitra Beton MandiriPekanbaru. 2) there was a positive and significant effect between the independentvariables (Occupational Safety and Health, Work Environment, and Workload)partially or individually on the dependent variable (Employees Performance) atPT. Mitra Beton Mandiri Pekanbaru, Keywords: Occupational Health and Safety, Work Environment, Workload,Employees Performance